Overcoming Vulnerabilities of Pension Systems - Fall, Falilou (OECD Economics Department Working Papers, 2014)
Demographic developments are unfavourable for the financing of pension schemes in most OECD countries, implying continued growth in pension expenditure in virtually all OECD countries. This paper examines the vulnerability of pension systems, with an emphasis on financial sustainability and adequacy. Policy trade-offs and complementarities are reviewed and flanking policies which could underpin successful pension reforms are examined. Automatic adjustment mechanisms are highlighted, as are the roles of prudential regulation and buffer or reserve funds in the case of shocks. Pension system vulnerability indicators are presented for all OECD countries, and the challenges and vulnerabilities of pensions systems in the BRIICS countries are reviewed